COMPUTATIONAL MODELING OF MEMBRANE TRANSPORTERS AND DRUG DELIVERY SYSTEMS - Xolmanova Zarina; Xudaykulova Hulkar; Sattarov Yorqin Karimovich (Modern American Journals, 2026)
Membrane transporters and drug delivery systems are central determinants of therapeutic efficacy, pharmacokinetics, and targeted treatment outcomes. Membrane transporters — including solute carrier (SLC) and ATP-binding cassette (ABC) families — regulate the influx and efflux of drugs and nutrients across biological membranes, influencing drug absorption, distribution, metabolism, and excretion (ADME). Simultaneously, advanced drug delivery systems, particularly nanocarriers, provide controlled, targeted release of therapeutics at the site of action, enhancing efficacy and minimizing toxicity. Computational modeling has become indispensable in elucidating mechanisms of transporter function and in optimizing drug delivery vehicles through in silico methods such as molecular dynamics, multi-scale simulations, machine learning, and continuum modeling. This review synthesizes recent computational approaches to modeling membrane transporters and drug delivery systems, highlighting key methodologies, applications, challenges, and future research directions.
Keywords: Membrane transporters; drug delivery systems; computational modeling; molecular dynamics; nanocarriers; multi-scale simulation; artificial intelligence